T(15-5t)=0

Simple and best practice solution for T(15-5t)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for T(15-5t)=0 equation:


Simplifying
T(15 + -5t) = 0
(15 * T + -5t * T) = 0
(15T + -5tT) = 0

Solving
15T + -5tT = 0

Solving for variable 'T'.

Move all terms containing T to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), '5T'.
5T(3 + -1t) = 0

Ignore the factor 5.

Subproblem 1

Set the factor 'T' equal to zero and attempt to solve: Simplifying T = 0 Solving T = 0 Move all terms containing T to the left, all other terms to the right. Simplifying T = 0

Subproblem 2

Set the factor '(3 + -1t)' equal to zero and attempt to solve: Simplifying 3 + -1t = 0 Solving 3 + -1t = 0 Move all terms containing T to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1t = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1t = 0 + -3 -1t = 0 + -3 Combine like terms: 0 + -3 = -3 -1t = -3 Add 't' to each side of the equation. -1t + t = -3 + t Combine like terms: -1t + t = 0 0 = -3 + t Simplifying 0 = -3 + t The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Solution

T = {0}

See similar equations:

| 0.5(x-3)=7 | | -8(t-2)-3(3t+1)=-4 | | 40*3= | | -25=4x+5 | | 19=-11+2x | | 2n+14-4n=26 | | 56x^2=79x-9 | | 3y+5=2x+1 | | 5x-3=3+2x | | 13-9x=-50 | | y+3=-11 | | 12=7x+25 | | 12x+124=-32 | | 79=7x+12 | | 120-11x=-34 | | x+4-5x=3 | | 0.20s+0.32=520s | | (8y-7x)(8y+7x)= | | 0.18M+16=40.54M | | 12-7x=-6 | | -9-5x=-54 | | 10-3t=4 | | 0.2b+9=0.5b+18 | | 3x*6=39 | | -2v(v-5)(v-6)=0 | | 7x(8-2)= | | 11k-5=9k+7 | | 11-46=n | | -3(4y-4)=2(1-7y)+11 | | 2ln(x)=21 | | 3k-5-10k=23-1k | | -2x-2=-6-2 |

Equations solver categories